The Inferiority of Rondasih in Minanto's Novel Kemelut Rondasih dan Dua Anaknya (The Turmoil of Rondasih and Her Two Children) - Supardi, Kholish Wibisono; Muhtarom, Imam Muhtarom; Sugiarti, Dewi Herlina (FKIP - Universitas Riau, 2025)
This study aims to analyze the inferiority experienced by the character Rondasih in Minanto's novel Kemelut Rondasih dan Dua Anaknya (The Turmoil of Rondasih and Her Two Children). The main focus of this study is to explore how Rondasih's feelings of inferiority affect her social interactions, decisions, and character development throughout the story. This study uses a qualitative approach with descriptive analysis methods. The subject of this study is the novel Kemelut Rondasih dan Dua Anaknya by Minanto, while the object of this study is inferiority based on Alfred Adler's psychological theory. The data collection techniques used in this study include observation, literature study, listening, note-taking, and conclusion analysis. The results of the study show that the character Rondasih reflects an inferiority complex in the form of indecision, fear, insecurity, shame, cowardice, a need for support, and feelings of helplessness. Rondasih's inferiority complex influences her decisions and relationships with other characters in the story. These findings are expected to provide a deeper understanding of the characters and psychological dynamics in the novel.